The subversion of Mill and the ultimate aim of nursing - Snelling, Paul C. (Nursing philosophy, 2018)
This is lightly edited and referenced version of a presentation given at the 20th International Philosophy of Nursing conference in Quebec on 23rd August 2016. Philosophical texts are not given the same prominence in nurse education as their more valued younger sibling, primary research evidence, but they can influence practice through guidelines, codes and espoused values. John Stuart Mill’s harm principle, found in On Liberty, is not a universal law, and only a thoroughgoing libertarian would defend it as such, though it, or its remnants, can be seen can be seen in policy documents. But its influence is weakening. Smoking bans in enclosed spaces were initially justified with other-regarding considerations, but judgements from unsuccessful legal challenges from patients in UK psychiatric hospitals rely on preventing harm to the smoker, even when smoking outside, which does not harm others. In the wake of legislation, no-smoking policies enacted by hospitals are becoming more aggressive, banning smoking both inside and outside, and extending the use of power gained through employment to prevent nurses assisting patients enjoy a lawful habit. Mill’s dictum has been subverted, and this speaks to the fundamental purpose of nursing. Should nurses collude and willingly exert their power for their version of the good of the patient? Or should they instead reaffirm values that support and facilitate life choices made by autonomous people? The paper supports the latter option, and this has wider application for nursing which can be illuminated, if not settled, by revisiting Mill and his famous dictum.